Sagittal Cephalometric Evaluation Without Point Nasion: Sagittal G-Triangle Analysis. Issue 2 (20th March 2022) - Li, Boxiu; Zhang, Zhuomin; Lin, Xinping; Dong, Yan
Abstract : Abstract: This study aims to introduce a new sagittal cephalometric measurement, the sagittal G-triangle analysis, to accurately and reproducibly assess the sagittal jaw relationship. Sagittal G-triangle analysis, which consists of angles AXK and BXK, is based on an equilateral triangle (Bo–X–K) constructed using 5 cephalometric landmarks (Ba, Bo, Po, Or, and G). To test the diagnostic efficiency of this analysis, pretreatment cephalometric radiographs of 120 female and 120 male Chinese patients were randomly selected. For each enlisted subject, angles SNA and SNB as well as angles AXK and BXK were measured and recorded. On the basis of the SNA and SNB results, subjects were categorized into 6 groups: maxillary retrognathism, normal maxilla, maxillary prognathism, mandibular retrognathism, normal mandible, and mandibular prognathism. The diagnostic efficiency of angles AXK and BXK were evaluated using various statistical tests. A high correlation was detected between angles SNA and AXK as well as between angles SNB and BXK. Female patients with angle AXK between −2.255° and 2.860° and male patients with angle AXK between −2.615° and 2.120° were considered to have a normal maxilla position. Female patients with angle BXK between −2.61° and 2.93° and male patients with angle BXK between −2.275° and 0.610° were considered to have a normal mandible position. In conclusion, sagittal G-triangle analysis could be used as an alternative method for the evaluation of the sagittal position of the maxilla and mandible in cephalometric analysis.